STUDI EFEKTIVITAS PELAKSANAAN PROYEK PENANGGULANGAN KEMISKINAN PERKOTAAN-REHABILITASI DAN REKONSTRUKSI MASYARAKAT DAN PERMUKIMAN BERBASIS KOMUNITAS (P2KP-REKOMPAK) DI KABUPATEN BANTUL, YOGYAKARTA - Sri Haryani; Imam Subkhan (Journal of Indonesian Economy and Business (JIEB), 2007)
Urban Poverty Eradication - Community Settlement Rehabilitation and Reconstruction Program (P2KP-REKOMPAK) was a World Bank funded project having aim to perform settlement reconstruction and rehabilitation of earthquake victim in Central Java and Yogyakarta. Through the project it will be built houses amount 4.080 units. The purpose of the project is not merely building houses, but it more to improve people consciousness to develop their community together by themselves. The research attempts to assess the effectiveness of the project implementation that was observed in four aspects i.e. target, institution, house building, and administration – finance. The research was conducted from December 15, 2006 to January 15, 2007 in 15 villages in Bantul District by survey method. In each village, were elected randomly three respondents consist of one represent BKM and two KSMP. Meanwhile, the villages of sample location was determined purposively that based on the most poverty house damaged. Instruments were used in the research consists of questioner and interview. Interview was performed to relevant parties with the project, i.e. village chief, facilitator, field coordinator and DMC Team Leader who have responsible for implementation of the project in Yogyakarta. In general, the research result showed that P2KP-REKOMPAK project implementation was effective in all aspect. Even though the aim to empowering community yet to be caused by dominant role of BKM and the function of people meeting (achieved) was not optimal.